2021
DOI: 10.1128/aem.00197-21
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Different Size Fractions Provides a More Complete Perspective of Viral Diversity in a Freshwater Embayment

Abstract: Inspired by recent discoveries of the prevalence of large viruses in the environment, we re-assessed the longstanding approach of filtering water through small pore-size filters to separate viruses from cells before metagenomic analysis. We collected samples from three sites in Hamilton Harbour, an embayment of Lake Ontario, and studied 6 datasets derived from < 0.45 μm and > 0.45 μm size fractions to compare the diversity of viruses in these fractions. At the level of virus order/family we observed high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 68 publications
2
11
1
Order By: Relevance
“…Since we analyzed sequences from DNA, our methodology excluded RNA viruses, which have a role in infecting eukaryotes in marine environments ( 42 ), while our analytical pipeline is biased toward Caudovirales bacteriophages and excludes single-stranded DNA (ssDNA) viruses ( 43 ), which predominate in some freshwater polar environments ( 44 ). Prefiltration of our water samples at 0.22 μm also causes us to miss a portion of the viral diversity ( 45 ), in particular by removing some nucleocytoplasmic large DNA viruses (NCLDVs), including Mimiviridae , and larger Phycodnaviridae ( 46 ). Prefiltration can result in underrepresentation of lysogenic viruses, which may be found as prophages within host cells; however, given that a previous study in a polar lake in summer found a lytic lifestyle predominated ( 16 ), we consider that the majority of the dsDNA viral diversity was likely present as free virions.…”
Section: Discussionmentioning
confidence: 99%
“…Since we analyzed sequences from DNA, our methodology excluded RNA viruses, which have a role in infecting eukaryotes in marine environments ( 42 ), while our analytical pipeline is biased toward Caudovirales bacteriophages and excludes single-stranded DNA (ssDNA) viruses ( 43 ), which predominate in some freshwater polar environments ( 44 ). Prefiltration of our water samples at 0.22 μm also causes us to miss a portion of the viral diversity ( 45 ), in particular by removing some nucleocytoplasmic large DNA viruses (NCLDVs), including Mimiviridae , and larger Phycodnaviridae ( 46 ). Prefiltration can result in underrepresentation of lysogenic viruses, which may be found as prophages within host cells; however, given that a previous study in a polar lake in summer found a lytic lifestyle predominated ( 16 ), we consider that the majority of the dsDNA viral diversity was likely present as free virions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in plaque assays, agar concentrations are often too high for larger phage particles to diffuse through compared to smaller particles [20]. Moreover, filters are often used to remove cells when preparing viral enrichments for metagenomic sequencing [21], which excludes larger viruses [9,22]. Particularly in marine studies, the <0.22 µm fraction, sometimes even referred to as the "viral fraction" [23], is most commonly examined for viruses [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in plaque assays, agar concentrations are often too high for larger phage particles to diffuse through compared to smaller particles [19]. Moreover, filters are often used to remove cells when preparing viral enrichments for metagenomic sequencing [20], which excludes larger viruses [9,21].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in plaque assays, agar concentrations are often too high for larger phage particles to diffuse through compared to smaller particles [ 20 ]. Moreover, filters are often used to remove cells when preparing viral enrichments for metagenomic sequencing [ 21 ], which excludes larger viruses [ 9 , 22 ]. Particularly in marine studies, the <0.22 µm fraction, sometimes even referred to as the "viral fraction" [ 23 ], is most commonly examined for viruses [ 24 26 ].…”
Section: Introductionmentioning
confidence: 99%